2021
DOI: 10.1126/sciadv.abg6856
|View full text |Cite
|
Sign up to set email alerts
|

Time-restricted feeding prevents deleterious metabolic effects of circadian disruption through epigenetic control of β cell function

Abstract: Time-restricted feeding improves glucose homeostasis through epigenetic control of pancreatic β cell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 85 publications
2
18
0
Order By: Relevance
“…Still, we show here and have shown previously that reconstituted peripheral clocks can overcome this altered context, especially with the addition of night feeding ( 8 ). For example, though pancreas BMAL1 regulates glucose-stimulated insulin secretion from beta cells and is a key peripheral node of the clock system with respect to feeding-fasting behavior ( 27 , 28 ), night feeding of Liver+Muscle-RE mice induced a serum insulin rhythm and rescued systemic glucose tolerance even in the absence of pancreas BMAL1. In addition, central clock reconstituted mice also exhibit improved glucose tolerance, at least in part due to reinstated feeding-fasting behavior ( 7 ).…”
Section: Feeding Rhythms Bolster Autonomous Liver and Muscle Clocks E...mentioning
confidence: 99%
“…Still, we show here and have shown previously that reconstituted peripheral clocks can overcome this altered context, especially with the addition of night feeding ( 8 ). For example, though pancreas BMAL1 regulates glucose-stimulated insulin secretion from beta cells and is a key peripheral node of the clock system with respect to feeding-fasting behavior ( 27 , 28 ), night feeding of Liver+Muscle-RE mice induced a serum insulin rhythm and rescued systemic glucose tolerance even in the absence of pancreas BMAL1. In addition, central clock reconstituted mice also exhibit improved glucose tolerance, at least in part due to reinstated feeding-fasting behavior ( 7 ).…”
Section: Feeding Rhythms Bolster Autonomous Liver and Muscle Clocks E...mentioning
confidence: 99%
“…This is consistent with the latest systematic review and a cross-sectional study showing that evening chronotype was associated with a worse cardiometabolic risk profile and a higher risk of diabetes, cancer, and depression [ 44 , 45 ]. The latest research showed circadian rhythm disruption perturbed glucose homeostasis through disruption of pancreatic β cell function and loss of circadian transcriptional and epigenetic identity [ 46 ]. However, the opposite result was found in MR analysis, in which the IVW estimate yielded a morning chronotype and had an adverse effect on type 2 diabetes (OR = 1.37, 95% CI: 1.09–1.72, p = 0.0068).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian disruption and shift work are environmental stressors characteristic of impaired feeding/fasting rhythms and have been directly linked to the development of islet failure in T2DM ( 22 , 162 ). Pancreatic islets isolated from circadian disrupted ( via constant light) mice exhibit complete ablation of circadian rhythms in both gene expression and chromatin accessibility ( 47 ). Providing further evidence that rhythmic feeding/fasting cycles drive islet transcription, tRF was shown to rescue transcriptional and epigenetic (chromatin accessibility) rhythms, despite global circadian disruption, of genes/loci annotated to pathways regulating circadian rhythms along with β-cell function (i.e., insulin secretion and exocytosis) and rest pathways (i.e., FoxO signaling, fatty acid metabolism) active during feeding and fasting, respectively.…”
Section: Islet Response To Time-dependent Regulation Of Food Intakementioning
confidence: 99%
“…This was followed by a series of studies demonstrating that "b-cell rest" or acute inhibition of insulin secretion, could restore b-cell function (first phase insulin secretion), insulin/Ca 2+ pulsatility, and insulin content in obesity and T2DM (144)(145)(146)(147)(148). Chronic bcell stimulation common to high fat feeding/obesity (149) and circadian disruption (21,22) result in both b-cell dysfunction and apoptosis which have been shown to be reversed by ADF (49,150), tRF (47,151,152), and a FMD (153). Specifically, a 12-week ADF regimen protected mice from HF diet induced b-cell dysfunction and failure (49), which was associated with enhanced GSIS, restored islet insulin content, and reduced apoptosis contingent on ADF activation of the autophagy-lysosome pathway.…”
Section: Islet Response To Time-dependent Regulation Of Food Intakementioning
confidence: 99%